National Heritages and the Law, A Book Review â€œPerlindungan Negara atas Warisan Budaya Bangsaâ€, Dr. Diah Imaningrum Susanti, S.H., M.Hum, M.Pd, Setara Press Malang, 2018, 192 Pages, ISBN: 978-602-6344-53-3 - Helmi, Hanif (Faculty of Law, Universitas Negeri Semarang, 2021)
The obligation to appoint a competent authority based on national provisions to provide protection for published works whose authors are not known to represent the interests of the creators and protect the rights of the creators is one of the problems in the context of protecting cultural heritage in the copyright dimension in Indonesia. The book